The effects of sedatıon wıth ıntravenous mıdazolam ın 1 oo patıents undergoıng upper gastroıntestınal endoscopy - Koç, Demet; Gençosmanoğlu, Rasim; Şad, Orhan; Tözün, Nurdan (My University, 2001)
Objective: The use of sedation in upper gastrointestinal endoscopy is widespread because of better patient tolerance. As this sedation is usually performed by nonanesthesiologists in and outside of hospital settings, possible adverse effects arising during the procedure must be dealt with carefully. In this study, the safety and efficacy of midazolam for conscious sedation in 100 patients undergoing upper gastrointestinal endoscopy were evaluated prospectively. Patients and Methods: Hundred consecutive patients undergoing upper gastrointestinal endoscopy were sedated with intravenous midazolam. The dose of midazolam was titrated according to the patient’s need and the duration of the procedure. Heart rate and oxygen saturation of all the patients were continuously monitored during the procedure and any complications were recorded. The amnesic effect of midazolam and patient comfort were also evaluated. Results: During the procedure, absence of oxygen desaturation (Sa02 > 95%) was found in 80%, mild oxygen desaturation (95% > Sa02 > 92%, at least 15 seconds duration) in 16%, and severe oxygen desaturation (Sa02 < 92%, at least 15 seconds duration) in 4%. Twenty-six patients had tachycardia only during the insertion of the endoscope, 17 patients had it throughout the procedure. Ventricular premature beats were recorded in two patients. Different degrees of amnesia were seen in 60% of the patients and the comfort level was excellent in 41%, good in 43%, and fair in 16%. Conclusion: Sedation of patients undergoing upper gastrointestinal endoscopy with intravenous midazolam results in better tolerance of the procedure. Routine monitoring must be provided because of the risks of desaturation and arrhythmia.
Keywords: Midazolam, Conscious sedation, Upper gastrointestinal endoscopy.